Komparasi Peranan Perempuan Lingkup Domestik dan Publik - Alwaris, Sri Ayu Andari Putri; M, Misbahuddin; Suhufi, Muh (Madani: Jurnal Ilmiah Multidisiplin, 2024)
This paper examines the role of women in the domestic and public spheres with the aim of providing an explanation regarding matters relating to the role women in the domestic and public spheres. This article is a literature review sourced from several relevant references to the topic discussed. Data collection techniques come from researching relevant reference sources in the from of journals, articles, websites, books and other scientific work. The analysis technique for this research is through collection, analysis and drawing conclusions. The results of the discussion of this article are: explained the role of women in the domestic sphere and explaining the role of women in the public sphere, namely looking at the role of women in the industrial revolution 4.0 womenn’s leadership in the fields of politic are education.